Proteus: um arcabouço para o particionamento de aplicações orientadas por objetos no ambiente da computação pervasiva - Andre Bigonha Toledo (2007)
In a pervasive environment, we have an abundance of computational devices capable to inter-communicate. These devices can be many times in idle state, which allows it to donate part of its resources to applications in other devices. This master thesis presents a model of distribution and a framework for development of distribution solutions for Java applications in pervasive environment. The framework enables centralized applications to be distributed for the devices of the environment, taking advantage of the available resources.